Pelaksanaan Hak Prerogatif Presiden dalam Penyusunan Kabinet Berdasarkan Pasal 17 UUD 1945 Amandemen Suatu Tinjauan Sistem Ketatanegaraan Indonesia - Sulkiah Sulkiah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2019)
Article 17 of Law-1945 assert that, granting prerogative to the president substantially limiting the powers of the president. Right as Prerogative. This can be understood broadly and narrowly. narrowly prerogative rights are only given to the president in choosing ministers - minister of state. While at large. not only the existance of the rights prerogative appointment and dismissal of ministers, but also includes the authority to run the gpvernment, ass well as matters state, including appoint ambassadors and conculs, granting pardons, amnesty, abolition and restoration, giving the title and decorations, but in the right order prerogative practice there are constraints, indicated the presence of interference from political parties support (coalitions). Under these conditions, the formulation of the problem as follows : 1 . How prerogative rights owned by the President in the preparation of the cabinet, before and after the amendment of the Act of 1945. 2. What is a constraint in implementing the prerogative of the President. The purpose of this study was to determine the effect of the application of constellation Political Rights prerogative President under Article 17 of Law - 1945. This writing method normative juridical approach. The problems in the implementation of rights prerogative president president 1 system generally occurs when the system is combined with a coalition with the party support multy-pertay system.Pasal 17 Undang- Undang Dasar 1945 menegaskan bahwa pemberian hak prerogatif kepada presiden. Hakekatnya pembatasan terhadap kewenangan Presiden dengan sebutan hak prerogatif. Hal ini dapat dipahami secara luas dan sempit. Secara sempit hak prerogatif hanya diberikan kepada presiden dalam hal memilih menteri-menteri negara, sedangkan secara luas keberadaan hak prerogatif tidak hanya pengangkatan dan pemberhentian menteri, tetapi juga termasuk kewenangan dalam menjalankan roda pemerintahan, serta urusan kenegaraan diantaranya mengangkat duta dan konsul, memberikan grasi, amnesti, abolisi, dan rehabilitasi, memberikan gelar dan tanda jasa. Namun dalam tatanan praktek hak prerogatif ini terdapat kendala, terindikasi adanya interpensi dari partai politik pendukung (koalisi).Berdasarkan hal tersebut maka rumusan permasalahan sebagai berikut: (1).Bagaimana hak prerogatif yang dimiliki oleh presiden dalam penyusunan kabinet. Sebelum dan sesudah adanya amandemen Undang-Undang Dasar 1945. (2).Apa yang menjadi kendala dalam melaksanakan hak prerogatif presiden. Tujuan Penelitian ini adalah untuk mengetahui pengaruh konstalasi Politik terhadap penerapan hak prerogatif presiden berdasarkan Pasal 17 Undang-Undang Dasar 1945. Penulisan ini menggunakan metode pendekatan yuridis normatif. Problematika penerapan hak prerogatif presiden pada sistem presidensial pada umumnya terjadi ketika dikombinasikan dengan sistem koalisi dengan partai-partai (sistem multi partai).